Obtaining mutant fungal strains of Aspergillus niger with high production of fructooligosaccharides (FOS) using ultraviolet light irradiation - Gutarra Castillo, Boris (2017)
A strain of Aspergillus niger PR-142 native to northern coast of Peru was subjected to successive processes of mutagenesis by ultraviolet light (UV) irradiation at 253.7 nm to increase the production of fructooligosaccharides (FOS). An initial selection was made by considering the mutants with increased invertase activity followed by the measurement of β-fructosyltransferase (FTase) activity both in mycelium and extracellular environment. Five selected mutants, which showed increased values of mycelium invertase activity (ranging from 101 to 128% as compared to the parent strain) at 40°C and sodium dodecylsulfate 0.15 (w/v), were grown in a fermentative medium in 50 mL conical tubes on a rotary shaker, and their FTase activity was determined. The 6-M69 mutant showed the most active mycelium activity of 1.5 fold as compared to the parent strain. When the same reaction was performed between 1 to 4 h, at the 3rd h, the mycelium FTase activity significantly increased up to 7 and 3 times in the mutant and parental strain, respectively. Finally, 4 mutants and the parental PR-142 were genetically characterized using inter simple sequence repeat polymerase chain reaction (ISSR-PCR) molecular markers. This analysis showed a significant 33% polymorphic bands between the parent and mutant markers, and 20 bands were unique to the mutants.